On the importance of relative salience: comparing overt selection behavior of single versus simultaneously presented stimuli. - Alisha Siebold; Mieke Donk (PLoS ONE, 2014)
The goal of the current study was to investigate time-dependent effects of the number of targets presented and its interaction with stimulus salience on oculomotor selection performance. To this end, observers were asked to make a speeded eye movement to a target orientation singleton embedded in a homogeneous background of vertically oriented lines. In Experiment 1, either one or two physically identical targets were presented, whereas in Experiment 2 an additional orientation-based salience manipulation was performed. The results showed that the probability of a singleton being available for selection is reduced in the presence of an identical singleton (Experiment 1) and that this effect is modulated by the salience of the other singleton (Experiment 2). While the absolute orientation contrast of a target relative to the background contributed to the probability that it is available for selection, the crucial factor affecting selection was the relative salience between singletons. These findings are incompatible with a processing speed account, which highlights the importance of visibility and claims that a certain singleton identity has a unique speed with which it can be processed. In contrast, the finding that the number of targets presented affected a target's availability suggests an important role of the broader display context in determining oculomotor selection performance.